GAME EDUKASI DENGAN MENGGUNAKAN UNITY 3D UNTUK MENUNJANG PROSES PEMBELAJARAN - Khaerudin, Muhamad; Srisulistiowati, Dwi Budi; Warta, Joni (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2021)
AbstractOne form of development of interactive learning media is learning media using games. Because games are quite popular among teenagers, by building learning media using games, it is hoped that it can help increase learning motivation and attract interest in learning with a fun learning process. This educational game is called Hinterweltlern with the RPG (Role Playing Game) genre, where a story is presented based on the basic competency material at each level. Students will explore dungeons, and can access materials by completing objectives/missions, killing enemies, or reaching the checkpoint area. Each level session has a Boss that must be defeated by answering questions correctly about the material that has been given to advance to the next level. The research method used in this study is the Research and Development (P&P) method. This educational game is a hybrid game with the genres of Role Playing Game, Fighting, Fantasy, and Education using Unity 3D software, which replaces the Conventional Learning Activity method with a more interactive and interesting method, namely a Windows Platform educational game. The result of making this Educational Game of Appearance is in the form of a 3-dimensional Game, the player where the player will act as a certain character who runs the plot according to the storyboard that has been made. Players will be asked to explore dungeons/chapters to run quests or access materials.Â Keywords : Instructional Media; Games; RPGs; Unity 3D;